Uncovering Injustices in the Green Transition: Sámi Rights in the Development of Wind Energy in Sweden - Dorothee Cambou (Arctic Review on Law and Politics, 2020)
This contribution is an analysis of how the rights of the Sámi to engage in reindeer husbandry are guaranteed in the green transition to renewable energy in Sweden. Consideration of the increasing number of court decisions addressing the impacts of wind energy on reindeer husbandry in Sweden raises significant questions about the fairness of the transition to sustainable development. The purpose of this analysis is to examine the impacts of wind energy on reindeer husbandry and uncover the justice issues raised by this development. Drawing on the discourse of just transition that includes distributional, procedural and recognition considerations, this analysis more specifically examines the distributive effects of the development of wind energy on reindeer husbandry and identifies how Sámi reindeer herders are included and their status and human rights as an Indigenous people recognised within this process. On this basis, the conclusion from this study is that systemic reforms of the Swedish system that take due consideration of the human rights of the Sámi as an Indigenous people must be implemented in order to ensure a transition to sustainable development that equally benefits Sámi reindeer herders and can therefore provide justice for all.